Konsep Nilai Tambah Syariah Berlandaskan Akhlak Qur’ani - Hasanah, Naimatul; Badria, Nuril (Rifa'Institute, 2023)
Value added is a key concept for measuring income to determine a company's performance. On the other hand, Sharia's added value is economic, intellectual and spiritual. This study aims to build the concept of sharia value added. Study, that is, research in which data collection is done by collecting data from a variety of literature. The results of this research are based on the Qur'anic morality, namely economic value added (in the form of money), mental and spiritual value added (in the form of altruistic feelings, joy and love, sense of brotherhood, justice, truth, honesty and trust, care for nature, and a sense of God's presence) are acquired, processed, and distributed in a lawful manner, and morality is ingrained in every aspect of life as the lifeblood to carry out that mission. increase. The owner of an important treasure, that is, the responsibility of God. Economic value added (in the form of money), mental and spiritual value added (in the form of altruistic feelings, joy and love, sense of brotherhood, justice, truth, honesty and trust, care for nature, and a sense of God's presence)